INCOME ANALYSIS OF KUB CHICKEN FARMING GIVEN DRAGON FRUIT (Hylocereus Polyrizhus) PEEL EXTRACT IN DRINKING WATER - A.F.S., Atmaza; Putri, B. R. T.; Siti, N. W. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
This study aims to determine the income of KUB chicken farming with dragon fruit peel extract ( Hylocereus polyrhizus ). This research was conducted for eight weeks at Sesetan Field Laboratory, Faculty of Animal Husbandry, Udayana University, Denpasar. The design used was a completely randomized design (CRD) consisting of 4 treatments and 4 replicates with a total of 80 KUB chickens used. The treatment given is drinking water without dragon fruit peel extract which is used as a control (P0), drinking water given 3% dragon fruit peel extract (P1), drinking water given 6% dragon fruit peel extract (P2), drinking water given 9% dragon fruit peel extract (P3). The observed variables include income analysis based on cost, revenue, income, R/C ration and BEP. The results of the showed that KUB chickens with 9% dragon fruit peel extract gave the best results with an income of Rp997,088,-/per period with an R/C ratio of 1,632. BEP production unit as much as 15,513 kg of live KUB Chickens, BEP selling price of KUB Chickens per kg of Rp26.687,-/kg live weight, BEP revenue of Rp1.521.172,-/period. Based on the results of the study, it can be concluded that KUB chicken farming by giving 9% dragon fruit peel extract (Hylocereus polirizhus) can increase the income of farmers.